Peningkatan Produktivitas Produksi Brem Sebagai Upaya Untuk Mengangkat Potensi Kabupaten Wonogiri - Y. Djoko Suseno; Edi Wibowo (WASANA NYATA, 2018)
Tengar Village Nguntonadi sub-district is one of brem-producing centers in Wonogiri region with high quality. However, in the management of brem production many experience barriers in addition to technology and marketing problems. The purpose of this community service activity is to transfer technology to improve the quality of brem production, and marketing management training to increase brem sales value. The method used is through training, mentoring to partners and monitoring although community service activities have been completed to maintain the sustainability of the program. The impact of community service activities is that there has been a transfer of technology from traditional to modern so that brem making becomes more hygienic and quality, as well as changes in marketing patterns from direct sales to sales through social media.Key words : Wonogiri’s brem, technology, marketing.